2020
DOI: 10.2116/analsci.20p200
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Synergistic Effect of L-Arginine on the Anticancer Activity of Doxorubicin by Using a Co-culture System

Abstract: In the early stage of tumor development, tumor associated macrophage (TAM) works to suppress tumor growth by secreting soluble factors including nitric oxide (NO). L-Arginine (Arg) is a substrate of nitric oxide synthase (NOS) expressed in TAM. Here we examined whether NO produced from Arg by macrophages works to enhance the effect of the anti-cancer drug, doxorubicin (Dox) by using co-culture system of cancer cells with macrophages. By employing colorimetric analyses methods (Griess Reagent and Cell Counting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It has been reported, that DOX increases the production of tumour necrosis factor (TNF), interleukin-1 (IL-1), interferon γ (IFNγ) and NO, therefore, increasing the tumoricidal potential of macrophage cells. 60,61 Another study 62 reported that the co-culture with Raw 264.7 cells reduced the viability and susceptibility to DOX of the three different cancer cell lines, which is consistent with our earlier findings.…”
Section: Nanoscale Papersupporting
confidence: 90%
“…It has been reported, that DOX increases the production of tumour necrosis factor (TNF), interleukin-1 (IL-1), interferon γ (IFNγ) and NO, therefore, increasing the tumoricidal potential of macrophage cells. 60,61 Another study 62 reported that the co-culture with Raw 264.7 cells reduced the viability and susceptibility to DOX of the three different cancer cell lines, which is consistent with our earlier findings.…”
Section: Nanoscale Papersupporting
confidence: 90%
“…21 NO production by macrophages incubated with Arg-LP NO production by macrophages using Arg as the substrate in response to lipopolysaccharides (LPS) stimulation has been reported. 18,22 Here, we evaluated NO production by macrophages incubated with Arg-LP. Macrophages were rst stimulated with LPS (1 mg mL À1 ) for 6 h to activate the expression of iNOS and then incubated with different amounts (dened as Arg concentration in mM) of Arg-LP for 48 h. The produced NO was detected by Griese reagent.…”
Section: Preparation Of Arg-containing Liposomes (Arg-lp)mentioning
confidence: 99%
“…Following the successful preparation of Arg-LP, we sought to encapsulate Dox into Arg containing liposomes by using a remote loading method to yield an efficient drug delivery system with reduced side effects. Based on our previous studies, 18,23 we hypothesized that combining Arg and Dox in a single delivery system should afford an efficient synergistic anticancer effect. Remote loading of Dox into liposomes was performed by using a pH gradient between the internal and external solutions.…”
Section: Preparation Of Dox-arg-lpmentioning
confidence: 99%
See 2 more Smart Citations